2018
DOI: 10.1192/bjp.2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen in the treatment of alcohol dependence with or without liver disease: multisite, randomised, double-blind, placebo-controlled trial

Abstract: Baclofen may be an effective treatment option for patients with ALD. However, given the profile of adverse events, the role for this medication might be best limited to specialist services.Declaration of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(115 citation statements)
references
References 42 publications
2
113
0
Order By: Relevance
“…While reduced resting vagal activity (i.e., HF‐HRV levels) is usually associated with less adaptability to situational demands (Laborde et al, ; Thayer et al, ), in this study high‐dose baclofen participants with lower resting vagal activity (shown through lower HF‐HRV) intriguingly demonstrated better drinking outcomes through reduced risky drinking. One potential explanation is that baclofen may have sedating effects (Leggio et al, ), particularly in higher doses when combined with alcohol (Evans & Bisaga, ; Morley et al, ). Considering a substantial proportion of the current study participants (around 70%) were still consuming alcohol during the treatment trial, baclofen and alcohol in combination may have reduced daily consumption for some high‐dose baclofen participants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While reduced resting vagal activity (i.e., HF‐HRV levels) is usually associated with less adaptability to situational demands (Laborde et al, ; Thayer et al, ), in this study high‐dose baclofen participants with lower resting vagal activity (shown through lower HF‐HRV) intriguingly demonstrated better drinking outcomes through reduced risky drinking. One potential explanation is that baclofen may have sedating effects (Leggio et al, ), particularly in higher doses when combined with alcohol (Evans & Bisaga, ; Morley et al, ). Considering a substantial proportion of the current study participants (around 70%) were still consuming alcohol during the treatment trial, baclofen and alcohol in combination may have reduced daily consumption for some high‐dose baclofen participants.…”
Section: Discussionmentioning
confidence: 99%
“…These dose‐specific associations between cue‐related HF‐HRV activity and prospective drinking outcomes suggest dose‐specific effects that have not yet been evidenced in clinical outcomes of baclofen RCTs. This includes the primary outcomes of this study's parent trial (Morley et al, ) and other randomized controlled studies, which do not demonstrate a higher dose‐specific response on reducing drinking outcomes (Beraha et al, ; Reynaud et al, ). Higher doses of baclofen (>60 mg/day) are not considered more efficacious in reducing alcohol consumption outcomes than lower doses, and patients generally demonstrate lower tolerability with higher doses (Pierce et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations